2017
DOI: 10.1158/1078-0432.ccr-17-1439
|View full text |Cite
|
Sign up to set email alerts
|

Hypermutated Circulating Tumor DNA: Correlation with Response to Checkpoint Inhibitor–Based Immunotherapy

Abstract: Purpose Tumor mutational burden detected by tissue next generation sequencing (NGS) correlates with checkpoint inhibitor response. However, tissue biopsy may be costly and invasive. We sought to investigate the association between hyper-mutated blood-derived circulating tumor DNA (ctDNA) and checkpoint inhibitor response. Experimental Design We assessed 69 patients with diverse malignancies who received checkpoint inhibitor-based immunotherapy and blood-derived circulating tumor DNA (ctDNA) NGS testing (54–7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(151 citation statements)
references
References 28 publications
(31 reference statements)
6
144
1
Order By: Relevance
“…Thirteen percent of the patients in this study had HNSCC. This study suggested that higher alteration number on ctDNA liquid biopsy is associated with a significantly improved response to checkpoint inhibitor‐based immunotherapy . This is consistent with findings from primary tissue biopsies.…”
Section: Introductionsupporting
confidence: 87%
“…Thirteen percent of the patients in this study had HNSCC. This study suggested that higher alteration number on ctDNA liquid biopsy is associated with a significantly improved response to checkpoint inhibitor‐based immunotherapy . This is consistent with findings from primary tissue biopsies.…”
Section: Introductionsupporting
confidence: 87%
“…NGS has unveiled useful genomic biomarkers for predicting diagnosis, prognosis, and response to cancer treatment . NGS can be performed on either tissue or blood‐derived ctDNA; these technologies may be complementary.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers for determining response to PD-1/PD-L1 blockade include PD-L1 expression, 1,2 microsatellite instability (MSI), 3 and a high tumor mutational burden (TMB). 4-6 …”
mentioning
confidence: 99%